Estimation of Vehicles Carbon Dioxide (CO2) Emission - Yunita Ismail; Anggy D Nurwidyawati; Atika D Rahayu (President University, 2019)
Transportation is a sector that has a dependency on fossil fuel production and will produce carbon dioxide (CO2) emissions. Carbon Dioxide (CO2) is a pollutant produced by vehicles which causes air pollution. The increase in vehicle demand causes an increase in CO2 emissions, which is the cause of global warming. But vehicles with fossil fuels are still a necessity for community mobilization. Because most vehicles used today are fossil fuel vehicles, the measurement of the efficiency of fossil fuel use is very important. The measure used to see the efficiency of fuel use by vehicles is Vehicle Kilometer Traveled (VKT). By using mobilev software, carbon dioxide (CO2) emissions from fossil fuel vehicles can be predicted. CO2 emissions that occur in an industrial area are caused by several types of motor vehicles, namely motorcycles, LDV and HDV cars. From the analysis of the correlation between CO2 emissions with each type of vehicle obtained that the motor and LDV have a strong correlation with CO2 emissions, but the correlation with HDV is weak. This shows that CO2 emissions from each vehicle will contribute to CO2 emissions, the number of motorcycles correlates very closely with CO2 emissions (r = 0.9), the number of LDV correlates closely with CO2 emissions (r = 0.7) and the number of HDV correlates weakly with CO2 emissions (r = 0.1).